Evaluation of the relationship between left atrial stiffness, left ventricular stiffness, and left atrioventricular coupling index in type 2 diabetes patients: a speckle tracking echocardiography study - Dang, Hai Nguyen Ngoc; Luong, Thang Viet; Ho, Binh Anh (Frontiers in Cardiovascular Medicine, 2024)
Background Cardiovascular complications are a leading cause of mortality and disability in individuals with diabetes mellitus (DM). Moreover, DM can directly impact the structure and function of cardiac muscle. We conducted a study to evaluate cardiac stiffness in DM patients in both the left atrium (LA) and left ventricle (LV), as well as to assess the impact of DM on the synchronization of the LA and LV, particularly within the Vietnamese population, utilizing speckle tracking echocardiography (STE). Methods We studied 111 research subjects divided into two groups comprising 52 patients with DM and 59 healthy individuals. All the subjects provided relevant clinical information, and echocardiography was performed to assess the indices of LA stiffness, LV stiffness, and left atrioventricular coupling index (LACI). Results Our study indicated that DM patients exhibited greater LA and LV stiffness than control patients. The LACI (%) in the DM group was also greater than that in the control group (17.12% ± 6.72% vs. 12.28% ± 3.96%, respectively; p < 0.001). The LACI was positively correlated with the LA and LV stiffness indices. Decreased levels of LV GLS, adjusted for age, sex, blood pressure, and BMI, have emerged as identified risk factors for DM. Conclusions LA stiffness, LV stiffness, and the LACI are greater in DM patients than in normal individuals.